Modelling environmental degradation in South Africa: the effects of energy consumption, democracy, and globalization using innovation accounting tests - Usman, Ojonugwa; Olanipekun, Ifedolapo O.; Iorember, Paul Terhemba; Abu-Goodman, Maryam (Springer Heidelberg, 2020)
This study investigates the effects of energy consumption, democracy and globalization on environmental degradation in the context of the environmental Kuznets curve (EKC) for South Africa between 1971 and 2014. To this end, the study applies the combined Bayer-Hanck cointegration test and the fully modified ordinary least squares (FM-OLS) estimation approach. The empirical results confirm the presence of cointegration among the variables, and thus validate the EKC hypothesis for South Africa. In addition, while energy consumption increases environmental degradation, the effect of democracy is positively insignificant. The finding also suggests that globalization condenses environmental degradation. The results of the long-run causal relationship divulge that economic growth, energy consumption, democracy and globalization Granger-cause environmental degradation. The results also find causality running from CO2 emissions, economic growth, democracy and globalization to energy consumption. In the short run, a causality is found running from globalization to CO2 emissions, energy consumption to CO2 emissions and globalization to energy consumption. In addition, economic growth is said to Granger-cause democracy while democracy Granger-causes CO2 emissions. These results are validated by the innovation accounting tests.
Keywords: Energy consumption; Democracy; CO2 emissions; Globalization index; Environmental Kuznets curve